The basement membrane zone in patients with systemic lupus erythematosus: immunofluorescence studies in the skin, kidney and amniochorion. - Alahlafi, A; Wordsworth, P; Lakasing, L; Davies, D; Wojnarowska, F (2004)
Histological studies suggest that the basement membrane zone (BMZ) is the main target of tissue pathology in cutaneous lupus erythematosus (LE). The BMZ is characteristically thickened and is the site of deposition of autoantibodies in LE. Alteration of some (BMZ) macromolecules is implicated in the pathology of several bullous skin diseases. A major component of BMZ is heparan sulphate proteoglycan (HSPG) which was found reduced in the skin of some patients with systemic lupus erythematosus (SLE) and in the kidney of mice with lupus nephritis. Similar to the skin, amnion is derived from the ectodermal germ layer during embryogenesis and expression of BMZ components of amniochorion was not previously studied in SLE. The aim of the present study was to investigate the expression of major BMZ macromolecules in the skin, kidney and amnioplacentae obtained from patients with SLE and compare these findings with organ biopsies from unaffected individuals. In addition, determining whether the differences in composition and distribution of BMZ macromolecules in these organs correlate with certain patterns of deposition of immunoreactants could contribute to our understanding of the mechanism of deposition of immunoreactants in SLE. In some patients with SLE, reduced expression of HSPG in nonlesional skin was reported previously. These changes of heparan sulphate might be important in the pathogenesis of LE. Therefore, the aims of this study are to confirm the previous finding and to compare HSPG expression between lesional and nonlesional LE skin. The unique features of each BMZ could contribute to the deposition or binding of positively charged immune complexes and explain the different patterns of immunofluorescence. Frozen sections of skin, kidney and amniochorion obtained from patients with SLE were investigated by indirect immunofluorescence technique using monoclonal antibodies (Moab) to determine the expression of major components of the BMZ. Heparan sulfate expression is reduced in the skin and, to a lesser extent, in the kidney in patients with SLE. There was no correlation between the kidney and skin heparan sulfate expression within the same patient. The BMZ composition in amniochorionic membrane ofplacentae from women with SLE was normal. Heparan sulfate may be one of the major targets for immunoglobulin deposition in the skin of patients with SLE. The processes of immunoglobulin deposition in SLE may be more complex in that there was no correlation between heparan sulfate expression in the skin and kidney of the same patient.